Fotovis: user-centered development of a tool for visually browsing photographic collections - Rabetti Giannella, Júlia (InfoDesign, 2021)
Fotovis is a tool for visualizing, exploring, and analyzing photographic collections. It is a partial result of a PhD thesis that investigated alternative, visual, and more generous browsing strategies — based on Digital Humanities — for digital tools. This paper discusses how Fotovis was conceived, developed (at the prototype level), and evaluated (at the interface level), through a user-centered approach and using a sample of photographs from the Moreira Salles Institute, an important Brazilian cultural entity. The goal is to highlight the definition of the users of Fotovis, and the design decisions that meet their exploratory and analytical needs.